2008
DOI: 10.1093/toxsci/kfn237
|View full text |Cite
|
Sign up to set email alerts
|

Parallelogram Approach Using Rat-Human In Vitro and Rat In Vivo Toxicogenomics Predicts Acetaminophen-induced Hepatotoxicity in Humans

Abstract: The frequent use of rodent hepatic in vitro systems in pharmacological and toxicological investigations challenges extrapolation of in vitro results to the situation in vivo and interspecies extrapolation from rodents to humans. The toxicogenomics approach may aid in evaluating relevance of these model systems for human risk assessment by direct comparison of toxicant-induced gene expression profiles and infers mechanisms between several systems. In the present study, acetaminophen (APAP) was used as a model c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
30
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(31 citation statements)
references
References 34 publications
1
30
0
Order By: Relevance
“…Furthermore, the correlations of the isoflavone supplementation effects between these species are weak, although they are statistically significant in a number of biological pathways, including the estrogen receptor pathway, known as the predominant route of biological activity of isoflavones. Our model provided quantitative data for the effect size in two tissues of two species and the correlation between these effect sizes that could be used in existing toxicological models, such as the parallelogram approach (Kienhuis et al, 2009a;Kienhuis et al, 2009c). However, to complete and verify this parallelogram approach and to draw a conclusion regarding possible health effects of isoflavones, data on gene expression in target tissue, i.e.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, the correlations of the isoflavone supplementation effects between these species are weak, although they are statistically significant in a number of biological pathways, including the estrogen receptor pathway, known as the predominant route of biological activity of isoflavones. Our model provided quantitative data for the effect size in two tissues of two species and the correlation between these effect sizes that could be used in existing toxicological models, such as the parallelogram approach (Kienhuis et al, 2009a;Kienhuis et al, 2009c). However, to complete and verify this parallelogram approach and to draw a conclusion regarding possible health effects of isoflavones, data on gene expression in target tissue, i.e.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have demonstrated the use of gene expression in the risk assessment of e.g. dibutyl phtalate (Euling et al, 2013a;Euling et al, 2013b;Makris et al, 2013), coumarin (Kienhuis et al, 2009a), acetaminophen (Kienhuis et al, 2009c) and benzo(a)pyrene .…”
Section: Introductionmentioning
confidence: 99%
“…Accordingly, in vitro to in vivo comparisons are necessary. By applying Omics technologies it is possible to measure similar endpoints of drug-induced changes between in vitro and in vivo which enable a global comparison of both models [4].…”
Section: Introductionmentioning
confidence: 99%
“…While the conventional assays generally measure only a limited set of biological endpoints, Omics technologies offers the possibility to measure multiple endpoints simultaneously in a single experiment. Currently, transcriptomics studies, where thousands of genes are measured simultaneously, have shown to be successful for this purpose [4][5][6]. However, transcriptomics investigates the relative mRNA levels of genes which often only moderately correlate with the relative abundance of their protein product.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies were rather discouraging. For example, Kienhuis et al (2009) reported that there is almost no overlap between gene expression alterations induced by paracetamol in the livers of rats compared to cultivated hepatocytes. To systematically address the possible in vitro/in vivo discrepancy, Heise and colleagues (Heise et al 2012) compared gene expression alterations induced by carcinogens in rat livers and in cultivated hepatocytes.…”
mentioning
confidence: 99%